Φ value analysis underscores strong functional and structural compactness of the GABA A receptor - Michał A. Michałowski; Katarzyna Terejko; Michalina Gos; Ilona Iżykowska; Marta M. Czyżewska; Karol Kłopotowski; Przemysław T. Kaczor; Aleksandra Brzóstowicz; Estera Płużek; Monika Migdałek; Jerzy W. Mozrzymas (Proceedings of the National Academy of Sciences, 2025)
γ-aminobutyric acid type A receptor (GABA A R) is a pentameric ligand-gated ion channel that plays a crucial role in inhibition in the adult brain. Structural and electrophysiological studies have provided numerous insights into the receptor’s functioning but the complete molecular mechanism of GABA A R action remains elusive. Herein, we used high-resolution single-channel recording to analyze point-mutated α 1 β 2 γ 2 receptors and applied so called Φ value (REFER, rate-equilibrium free energy relationship) analysis which allows to infer the order of domains engagement during activation, offering a complementary “dynamic” insight into the receptor’s function. As anticipated, point mutations at the orthosteric binding sites reduced GABA binding affinity, with the magnitude of this effect diminishing progressively with increasing distance from the binding site. On the contrary, mutations located all over the macromolecule’s structure, e.g., in “peripheral top position,” extracellular/transmembrane interface, and channel pore, affected the receptor with a clear tendency to influence entire gating including opening/closing, preactivation, and desensitization with no clear correlation with the distance to the channel gate. Interestingly, the calculated Φ values for the GABA A R showed a relatively narrow range (0.42 to 0.81), suggesting that the conformational transitions are highly synchronized and coordinated by a global network of interactions. This prediction is also in agreement with observation that, typically, single GABA A R residue mutation alters the kinetics of not just one but many (often all) conformational transitions. We thus propose a dictum reflecting modus operandi of the GABA A R: Binding is local and gating is global. In conclusion, our analysis indicates that GABA A R shows particularly strong functional compactness manifested as global gating mechanisms and high allostery.